Influence of the corpuscular theory in epistemology of John Locke - Lucas Cabello, Arturo (2015)
Locke for his academic studies and his proximity to the scientific work of the natural philosophers, substantially by the link that he had with Robert Boyle’s experimental philosophy, had direct knowledge of the development of the chemistry and physics and all the rise of science in the in the middle of the 17TH century. The wisemen of natural philosophy took as valid the Corpuscular theory to explain the phenomena of reality, one of these was the empiricist philosopher John Locke. In fact, Locke recognized that the internal structure of things were small corpuscular, and with the attitude of a metaphysical realist, recognized his objectivity as something external to perception. Nevertheless, he was skeptical at the epistemological level considering that these particles for being small and insensitive they weren’t available to the cognoscente subject.